2019
DOI: 10.1002/jat.3902
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the 4‐week repeated‐dose oral toxicity and genotoxicity of GHX02

Abstract: Herbal medicines are widely utilized for disease prevention and health promotion. GHX02 consists of mixtures including Gwaruin (Trichosanthes kirilowii), Haengin (Prunus armeniaca), Hwangryeon (Coptis japonica) and Hwangkeum (Scutellaria baicalensis). It has been purported to have therapeutic effectiveness in cases of severe bronchitis. Non‐clinical safety testing comprised a single‐dose oral toxicity study and a 28‐day repeated‐dose oral toxicity study with a 14‐day recovery period, and genotoxicity was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Moreover, a series of preclinical studies showed that GHX02 reduced airway inflammation, sputum production, cough, suppressed PM10D-induced inflammatory symptoms in the lung ( Yang et al, 2020 ), and had an anti-COPD effect ( Yang et al, 2018 ). Additionally, the safety of GHX02 has been verified in the assessment of 4-weeks repeated-dose oral toxicity and genotoxicity ( Ji et al, 2020 ). Although there are many animal studies and clinical experiences, there have been no clinical trials in humans that evaluate GHX02.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a series of preclinical studies showed that GHX02 reduced airway inflammation, sputum production, cough, suppressed PM10D-induced inflammatory symptoms in the lung ( Yang et al, 2020 ), and had an anti-COPD effect ( Yang et al, 2018 ). Additionally, the safety of GHX02 has been verified in the assessment of 4-weeks repeated-dose oral toxicity and genotoxicity ( Ji et al, 2020 ). Although there are many animal studies and clinical experiences, there have been no clinical trials in humans that evaluate GHX02.…”
Section: Introductionmentioning
confidence: 99%